USING STORYTELLING TO ENHANCE ENGLISH LANGUAGE SKILLS IN KIDS - Ruzieva Umida (World Scientific Research Journal, 2025)
Abstract: Storytelling is a powerful pedagogical tool that significantly enhances English language skills in children. This paper explores the multifaceted benefits of storytelling, including vocabulary acquisition, listening comprehension, and narrative skills. Through engaging narratives, children are exposed to rich language input, which fosters their linguistic development and creativity. The integration of storytelling into language learning not only captivates young learners but also promotes cultural awareness and emotional intelligence. This study reviews various methodologies for implementing storytelling in educational settings and highlights successful case studies demonstrating its effectiveness. Ultimately, the findings underscore the importance of storytelling as a dynamic approach to improving English language proficiency among children.